Targeting cytokine- and therapy-induced PIM1 activation in preclinical models of T-cell acute lymphoblastic leukemia and lymphoma - De Smedt, Renate; Morscio, Julie; Reunes, Lindy; Roels, Juliette; Bardelli, Valentina; Lintermans, Beatrice; Van Loocke, Wouter; Almeida, Afonso; Cheung, Laurence; Kotecha, Rishi; Mansour, Marc R; Uyttebroeck, Anne; et al. (AMER SOC HEMATOLOGY, 2020)
T-cell acute lymphoblastic leukemia (T-ALL) and T-cell acute lymphoblastic lymphoma (T-LBL) are aggressive hematological malignancies that are currently treated with high-dose chemotherapy. Over the last several years, the search toward novel and less-toxic therapeutic strategies for T-ALL/T-LBL patients has largely focused on the identification of cell-intrinsic properties of the tumor cell. However, non-cell-autonomous activation of specific oncogenic pathways might also offer opportunities that could be exploited at the therapeutic level. In line with this, we here show that endogenous interleukin 7 (IL7) can increase the expression of the oncogenic kinase proviral integration site for Moloney-murine leukemia 1 (PIM1) in CD127+ T-ALL/T-LBL, thereby rendering these tumor cells sensitive to in vivo PIM inhibition. In addition, using different CD127+ T-ALL/T-LBL xenograft models, we also reveal that residual tumor cells, which remain present after short-term in vivo chemotherapy, display consistent upregulation of PIM1 as compared with bulk nontreated tumor cells. Notably, this effect was transient as increased PIM1 levels were not observed in reestablished disease after abrogation of the initial chemotherapy. Furthermore, we uncover that this phenomenon is, at least in part, mediated by the ability of glucocorticoids to cause transcriptional upregulation of IL7RA in T-ALL/T-LBL patient-derived xenograft (PDX) cells, ultimately resulting in non-cell-autonomous PIM1 upregulation by endogenous IL7. Finally, we confirm in vivo that chemotherapy in combination with a pan-PIM inhibitor can improve leukemia survival in a PDX model of CD127+ T-ALL. Altogether, our work reveals that IL7 and glucocorticoids coordinately drive aberrant activation of PIM1 and suggests that IL7-responsive CD127+ T-ALL and T-LBL patients could benefit from PIM inhibition during induction chemotherapy.